2-(2-Phenylethyl)chromones increase in Aquilaria sinensis with the formation of agarwood - Sun, Yuanyuan; Wang, Meiran; Yu, Meng; Feng, Jian; Wei, Jianhe; Liu, Yangyang (Frontiers in Plant Science, 2024)
Obtained from Aquilaria Lam. and Gyrinops Gaertn., agarwood is a prestigious perfume and medicinal material in the world. Its primary chemical constituents and indicators of agarwood's development are 2-(2-phenylethyl)chromones (PECs). However, how PECs affect its quality, accumulation, and transformation pattern is still unclear. Thus, this study monitored resin filling in agarwood generated by the whole-tree agarwood-inducing technique (Agar-Wit) over a span of a year, observed the ethanol extract concentration at different sampling times, and statistically examined PECs in agarwood from each sampling period. The resin accumulated over time, except during the 4th–6th month due to the creation of a barrier layer. The relative content of total PECs demonstrated an overall increase throughout the year but a decrease from the 4th month to the 6th month, and the relative content of 19 PECs that persisted throughout the year was positively correlated with the content of ethanol extracts. In addition, the process of chromone accumulation was accompanied by the production and transformation of different types of chromones, with flindersia type 2-(2-phenylethyl)chromones (FTPECs), epoxy-2-(2-phenylethyl)chromones (EPECs), and diepoxy-2-(2-phenylethyl)chromones (DEPECs) being the major chromone components; in addition, the content of 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones (THPECs) kept increasing after 6 months of agarwood formation. Three main trends were identified from 58 analogs of PECs, each with notable variation. The first type had the highest content at the beginning of resin formation. The second type had the highest content at 6 months and then started to decrease, and the third type had a slowly increasing content. As a whole, this study systematically investigated the accumulation of PECs during injury-induced agarwood production in A. sinensis, which is of scientific significance in resolving the transformation of PECs and revealing the secret of agarwood formation.